Quality of life in patients with erythema nodosum leprosum in Kuala Lumpur, Malaysia - Felix B Yap; Sze T Kiung; Jeffrey B Yap (Indian Dermatology Online Journal, 2016)
Background: There is a paucity of data on quality of life issues in patients with leprosy suffering from erythema nodosum leprosum (ENL). Thus, we aim to study the effect of ENL on quality of life. Materials and Methods: This cross-sectional study was conducted in Hansen's Clinic, Hospital Kuala Lumpur between January 2010 and December 2013 among patients with multibacillary leprosy using the Dermatology Life Quality Index (DLQI). Results: A total of 153 patients participated with 31.4% suffering from ENL. The mean age at presentation was 40.5 ± 16.49 years. The mean DLQI was 7.1 ± 3.72. Patients with ENL were younger (mean age 36.5 vs. 42.4, P = 0.026), had higher mean bacteriologic index (4.3 vs. 3.8, P = 0.004), had physical deformities (47.9% vs. 31.4%, P = 0.049), and had higher mean DLQI score (9.1 vs. 6.2, P < 0.001). All the DLQI domains were higher in patients suffering from ENL except the treatment domain. Symptoms and feeling was the domain with the largest effect followed by daily activities and leisure. Personal relationship had the lowest effect. Conclusion: Quality of life impairment in patients with leprosy in Malaysia is moderate, with larger effect among patients with ENL. The impairment in ENL is comparable to itchy skin conditions such as urticarial and is worse than chronic skin disease such as psoriasis. Thus, it is essential that management of leprosy incorporate quality of life issues.